Left Atrial Appendage Transcatheter Occlusion with AMPLATZER™ Amulet™ Device: Real Life Data with Mid-Term Follow-Up Results - Mehmet Levent Şahiner (Arquivos Brasileiros de Cardiologia)
Abstract Background: Left atrial appendage (LAA) occlusion is an alternative therapy for atrial fibrillation patients who have high embolic risk and contraindications to anticoagulant therapy. Objective: To evaluate the feasibility, safety, and mid-term outcomes of percutaneous LAA occlusion, including device-related thrombosis. Methods: Sixty consecutive patients who had undergone percutaneous LAA occlusion with AMPLATZER™ Amulet™ device from September 2015 to March 2018 were enrolled. Patients were followed for 21 ± 15 months (median - 20 months, interquartile range - 9 to 27 months). The postprocedural assessment was done at the 1(st), 6(th), and 12(th) month. Patients were clinically evaluated, and transesophageal echocardiography was performed at each visit. We evaluated the condition of normality of variables using the Kolmogorov-Smirnov test. P-values < 0.05 were statistically significant. Results: The most common indication for the procedure was major bleeding with anticoagulants (n: 53, 88.3%). The procedure was completed successfully in 59 (98.3%) patients. Periprocedural mortality was observed in one patient. Postprocedural antiplatelet treatment was planned as dual or single antiplatelet therapy or low-dose anticoagulant therapy in 52 (88.1%), 2 (3.4%), and 5 (8.5%) patients, respectively. We found no clinically significant cerebrovascular events, device-related thrombus, or embolization in any patient during the follow-up. Two (3.4 %) patients presented significant peri-device leak (>3 mm) at the 1st month evaluation, which disappeared at the 12th month follow-up. Conclusion: We concluded that LAA occlusion using the Amulet™ LAA occluder can be performed with high procedural success and acceptable outcomes.